Предмет: Алгебра,
автор: мопс26
найдите значение выражения : x(2х-1)-(6+х)(х-6)+(х+10)(10-х ) при х =-101
Ответы
Автор ответа:
0
x(2х-1)-(6+х)(х-6)+(х+10)(10-х) = x(2х-1)-(х+6)(х-6)+(10+х)(10-х ) =
= 2х²-х-х²+36+100-х²=136-х
х=-101
136-(-101)=136+101=237
= 2х²-х-х²+36+100-х²=136-х
х=-101
136-(-101)=136+101=237
Похожие вопросы
Предмет: Химия,
автор: Аноним
Предмет: История,
автор: pdereza979
Предмет: Английский язык,
автор: dfffw
Предмет: Математика,
автор: gulzazak
Предмет: Математика,
автор: Can4eck0